Evaluación de los residuos agrícolas cascarilla de arroz (Oryza sativa) y bagazo de caña de azúcar (Saccharum officinarum) como sustrato para sistemas acuapónicos - Farías Mera, Mauricio Andrés (2024)
Waste generated from agricultural residues has become a concern for society and the environment, as it is not properly utilized and its production increases exponentially to meet the needs of the population. The research aims to evaluate agricultural residues of rice husk (Oryza sativa) and sugarcane (Saccharum officinarum) as substrates to improve crop yield in aquaponic systems. It was carried out in 2023, at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. A Completely Randomized Block Design was applied, with three treatments and three repetitions, totaling nine experimental units evaluated based on the substrate dose applied in each. Bibliographic, deductive, and experimental methods were used, with the application of observation, laboratory analysis, and inferential statistics techniques. The expected outcomes include the diagnosis of the bromatological characteristics of rice husk and sugarcane agricultural residues for their use as substrates, the determination of the efficiency of these agricultural residues as substrates to optimize the performance of aquaponic systems, and the calculation of costs and benefits of implementing these agricultural residues as substrates in aquaponic systems for commercial use.